Parametric Studies of Directed Fragmentation Warhead Used for Combat Shaped Charges - Robert PANOWICZ; Jacek NOWAK; Marcin KONARZEWSKI; Tadeusz NIEZGODA (Engineering Transactions, 2015)
The aim of this paper is to present the results of research on the influence of fragmentation liner material parameter on spreading capabilities. A fragmentation liner is a part of a directed fragmentation warhead used to combat shaped charges and consisting of metal balls embedded in the resin. In addition, the case of the fragmentation warhead and the surrounding air were also modeled. Four variants of numerical analyses were prepared, differing in the value of maximum plastic strain characterizing the fragmentation liner. C-4 explosive was used for driving the liner fragmentation. In order to properly describe the behaviour of the fragmentation warhead, Arbitrary-Lagrangian Eulerian (ALE) and Fluid-Structure Interaction (FSI) approach was used. A three dimensional model of directed fragmentation warhead along with the fragmentation liner was prepared in MSC Patran software and numerical analyses were performed using LS-Dyna software. As a result of numerical analyses, the maximum velocity and a spreading angle in both the vertical and horizontal plane of the fragmentation liner were determined in each case.